2020
DOI: 10.12659/msm.919220
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of RKI-1447 in a Mouse Model of Nonalcoholic Fatty Liver Disease Induced by a High-Fat Diet and in HepG2 Human Hepatocellular Carcinoma Cells Treated with Oleic Acid

Abstract: Background: This study aimed to investigate the effects of RKI-1447, a selective inhibitor of Rho-associated ROCK kinases, in a mouse model of nonalcoholic fatty liver disease (NAFLD) induced by a high-fat diet, and in oleic acid-treated HepG2 human hepatocellular carcinoma cells in vitro. Material/Methods: Four study groups of mice included: the control group; the high-fat diet (HFD) group; the HFD+RKI-1447 (2 mg/kg) group; and the HFD+RKI-1447 (8 mg/kg) group. Mice were fed a high-fat diet for 12 weeks. Mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…After the mice with NAFL acquired 5 mg/kg of H-bihistidine treatment for 7 consecutive days, the sera were obtained for transaminase activity and lipid content calculation. The results revealed that the ALT and AST levels were significantly elevated in the fatty liver mice (Figure 5A,B), suggesting that the high-fat-diet-induced liver injury in mice was in agreement with a previous report [16]. After H-bihistidine administration, transaminase activities decreased close to the control levels (Figure 5A,B).…”
Section: H-bihistidine Reduced Serum Transaminase and Lipid In Vivosupporting
confidence: 91%
“…After the mice with NAFL acquired 5 mg/kg of H-bihistidine treatment for 7 consecutive days, the sera were obtained for transaminase activity and lipid content calculation. The results revealed that the ALT and AST levels were significantly elevated in the fatty liver mice (Figure 5A,B), suggesting that the high-fat-diet-induced liver injury in mice was in agreement with a previous report [16]. After H-bihistidine administration, transaminase activities decreased close to the control levels (Figure 5A,B).…”
Section: H-bihistidine Reduced Serum Transaminase and Lipid In Vivosupporting
confidence: 91%
“…In support of this, the experimental evidence has demonstrated that selective delivery of the ROCK inhibitor to HSCs reduces chronic carbon tetrachloride (CCl4)-induced liver fibrosis or cirrhosis by inhibiting activated HSCs in mice [ 38 , 39 ], highlighting an essential role for ROCK action in HSCs. Similar observations have been found in various animal models, including HFD-fed mice [ 40 ], HFD and streptozotocin (STZ)-treated rats [ 41 ], STZ-induced diabetic rats [ 42 ], dimethylnitrosamine- induced hepatic fibrosis rats [ 43 ], and endotoxintreated mice [ 44 , 45 ]. In animal models of CCl4-induced liver fibrosis, the ability of a ROCK inhibitor to reduce HSCs activation is greatly enhanced, leading to the prevention of liver fibrosis development [ 39 , 46 - 48 ].…”
Section: Rho-kinase Inhibitor Ameliorates Nonalcoholic Fatty Liver Diseasessupporting
confidence: 79%
“…Since the introduction of this work, numerous studies have consistently revealed that ROCK inhibition is beneficial for multiple cardiovascular-related illnesses [32][33][34]. Beyond these investigations, a pharmacotherapy with the ROCK inhibitor has also been found to be effective in treating liver diseases, including NAFLD, NASH, and fibrosis as shown in Table 1 [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Data supporting a role of ROCK on liver diseases include the fact that a ROCK chemical inhibitor ameliorated hepatic steatosis and fibrosis in rats fed a choline-deficient/L-amino acid-defined (CDAA) diet and choline-deficient diet [35][36][37].…”
Section: Rho-kinase Inhibitor Ameliorates Nonalcoholic Fatty Liver Diseasesmentioning
confidence: 99%
“…These metabolic improvements were mediated through the activation of AMPK pathway in liver and skeletal muscle which contributed to increased whole body energy expenditure ( 47 , 48 ). In addition to systemic metabolic improvements, treatment with ROCK inhibitors ameliorates liver fibrosis in diabetic non-alcoholic steatohepatitis ( 178 – 180 ).…”
Section: Metabolic Roles Of Liver Skeletal Muscle Brain and Vascular ...mentioning
confidence: 99%